Unlocking the potential plant growth‐promoting properties of chickpea (Cicer arietinum L.) seed endophytes bio‐inoculants for improving soil health and crop production. (8th August 2021) - Mukherjee, Arpan; Gaurav, Anand Kumar; Patel, Amit Kumar; Singh, Saurabh; Chouhan, Gowardhan Kumar; Lepcha, Ayush; Pereira, Arthur Prudêncio de A.; Verma, Jay Prakash
Abstract: Sustainable agronomic practices are tried all over the world to promote safe and eco‐friendly crop production. Therefore, in the present study, the effect of seed endophytic bacteria and its consortium on soil biochemical property and yield of chickpea ( Cicer arietinum L.) under field and pot conditions are investigated. Both the experimental results proved a significant increase in total soil organic carbon (OC), electric conductivity (EC), organic matter (OM), and soil nutrients like available N, P, and K content and important soil enzymes like dehydrogenase (DHA), beta glucosidase, alkaline phosphate, urease, and microbial population in soil was observed under the Enterobacter hormaechei BHUJPCS‐15 (T1 ), Enterobacter cloacae BHUJPCS‐21 (T2 ), and combined T3 (consortium of T1 and T2 ) treatments. Similarly, a significant increase in the grain yield (27–45% and 57–73%) in microbial treatment was found in pot and field experiments, respectively, than in control. In addition, whereas the higher plant biomass (14–38% and 42–78%) was recorded in treated plant over the control plant. Similarly, the plant photosynthetic pigments (Chl a, b, total Chl) were increased in microbial treated plant than the control untreated chickpea plant. Consortium of endophytes were recorded effective result for enhancing plant growth attributes, productivity, and soil health. The consortium can be further used as biofertilizers for sustainable chickpea production. Our present study highlights the significance of sustainable agronomic practices for improving the soil quality and agricultural yield while reducing adverse impacts of chemicals by the use of seed endophytic microbes and its consortium.